Center pressure for bio-based lubricant in elastohydrodynamic lubrication of rectangular conjuction - Nor Faizah Haminudin, 1984-; Jamluddin Md. Shefiff, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2010